2013
DOI: 10.1017/s0263574713001008
|View full text |Cite
|
Sign up to set email alerts
|

Tension distribution shaping via reconfigurable attachment in planar mobile cable robots

Abstract: Traditional cable robots derive their manipulation capabilities using spooling winches at fixed base locations. In our previous work, we examined enhancing manipulation capabilities of cable robots by the addition of base mobility to spooling winches (allowing a group of mobile robots to cooperatively manipulate a payload using cables). Base mobility facilitated the regulation of the tension-direction (via active coordination of mobile bases) and allowed for better conditioning of the wrench-feasible workspace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Recently in several papers, reconfigurable or adaptive CDPRs have been investigated. 1217 The idea of configuration adaptability is presented to formalize a new methodology for design of CDPRs. 13 According to this method an optimum design solution to maximize or minimize particular local performance criteria such as cable tension factor and dexterity of CDPRs is achieved based on separating cable disposition and pose of end-effector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently in several papers, reconfigurable or adaptive CDPRs have been investigated. 1217 The idea of configuration adaptability is presented to formalize a new methodology for design of CDPRs. 13 According to this method an optimum design solution to maximize or minimize particular local performance criteria such as cable tension factor and dexterity of CDPRs is achieved based on separating cable disposition and pose of end-effector.…”
Section: Introductionmentioning
confidence: 99%
“…Although the robot utilizes few number of cables, it achieves acceptable force capabilities since it benefits semiadaptive design of the CDPR in which one of the pulleys is allowed to move. In Zhou et al., 15 an outline to study reconfigurable CDPRs is presented. The proposed method investigates improvement of tension distribution by solving reconfiguration of such systems according to a tension factor over the workspace.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Zhou et al [23] suggested to increase the number of Degrees of Freedom (DOFs) of CDPRs by mounting the winches on mobile bases, which results in a type of RCDPRs. In [24,25], Zhou used an alternative concept for RCDPRs. A set of cables with constant lengths are connected to linear motors.…”
Section: Introductionmentioning
confidence: 99%
“…A set of cables with constant lengths are connected to linear motors. The cables are either attached to the platform [25] or pull the platform by means of idler pulleys [24]. In both cases, a planar case study has been investigated to show the concept advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Izard et al [16] also studied a family of RCDPRs for industrial applications. Rosati et al [32,36] and Zhou et al [38,39] focused their work on planar RCDPRs. Recently, Nguyen et al [27,26] proposed reconfiguration strategies for large-dimension suspended CDPRs mounted on overhead bridge cranes.…”
Section: Introductionmentioning
confidence: 99%